Recent Advances in Antiinflammatory Material Design. Issue 1 (13th October 2020) - Lebaudy, Eloïse; Fournel, Sylvie; Lavalle, Philippe; Vrana, Nihal Engin; Gribova, Varvara
Abstract: Implants and prostheses are widely used to replace damaged tissues or to treat various diseases. However, besides the risk of bacterial or fungal infection, an inflammatory response usually occurs. Here, recent progress in the field of anti‐inflammatory biomaterials is described. Different materials and approaches are used to decrease the inflammatory response, including hydrogels, nanoparticles, implant surface coating by polymers, and a variety of systems for anti‐inflammatory drug delivery. Complex multifunctional systems dealing with inflammation, microbial infection, bone regeneration, or angiogenesis are also described. New promising stimuli‐responsive systems, such as pH‐ and temperature‐responsive materials, are also being developed that would enable an "intelligent" antiinflammatory response when the inflammation occurs. Together, different approaches hold promise for creation of novel multifunctional smart materials allowing better implant integration and tissue regeneration. Abstract : Implants and prostheses are widely used nowadays to replace damaged tissues or to treat various diseases. However, besides the risk of bacterial or fungal infection, an inflammatory response usually occurs. Here, recent progress in the field of anti‐inflammatory biomaterials is described. Together, different approaches hold promise for creation of novel multifunctional smart materials allowing better implant integration and tissue regeneration.